Approach to Crime among the Incas - Pease, Franklin (1971)
In contrast to the modern legal systems that have been established throughout history, the Incas conceived as a crime not the transgression of a legal norm per se, but the alteration of a sacred order represented by the gods and the Inca. For this reason, in most cases, the sanction or punishment of the guilty party was based on the expiation of the crime that sought to recover the social equilibrium. To that extent, the objective of this article is to analyze the way in which the Incas understood and punished crime. For this reason, the author analyzes the different types of crimes, classifying them into four groups: (i) crimes against the state, the cult and the Inca, (ii) crimes against the person, (iii) crimes affecting property and (iv) sexual crimes. The author also points out that the Inca legal conception cannot be compared, nor measured, with the European conception since both are completely different and, therefore, evaluate crime differently.